2021
DOI: 10.23887/jpp.v54i2.34639
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of Learning Media through Digital Book Development Using the Flipbook Application

Abstract: The development and advancement of information and communication technology that penetrates various fields of human life had enormous potential to be used, therefore it was important to integrate thoroughly between technology into the learning process. This study aims to develop a flipbook-based digital as an instructional media that was suitable for the learning activities. This research approach was research and development (RnD) with the ADDIE as a development model which consists of Analysis, Design, Devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…The category of media validation will be shown by the calculation's percentage findings. The criteria for deciding the feasibility of multimedia simulation are used as bases of evaluation and the foundation for improving multimedia adjusts from several reference sources, such as research by Bustanil et al (2019) and Perdana et al (2021). The control and experimental classes are divided into the pre-test and post-test.…”
Section: Discussionmentioning
confidence: 99%
“…The category of media validation will be shown by the calculation's percentage findings. The criteria for deciding the feasibility of multimedia simulation are used as bases of evaluation and the foundation for improving multimedia adjusts from several reference sources, such as research by Bustanil et al (2019) and Perdana et al (2021). The control and experimental classes are divided into the pre-test and post-test.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Suryani & Khoiriyah (2018) conclude that e-books can be used as a source of independent learning for students who do not have printed books and can be used as an alternative/additional reference for teachers if there is a shortage of face-toface meetings in class but the material presented is not available in the classroom. school printed books; (4) Yulaika et al (2020) concluded that the use of flip book-based electronic teaching materials in economic learning had a positive impact on improving student learning outcomes and increasing student activities including visual, oral, listening, writing, and emotional; (5) Mentari et al (2018) concluded that after the e-book was implemented on 30 students, it showed that 19 students thought very creatively (63%), 7 students thought creatively (23.3%), and 3 students think creatively enough (13,3%); (6) Utami & Ducha (2020) concluded that flipbook can help students to understand abstract material and practice students' critical thinking skills; (7) Perdana et al (2021) concluded that the flipbook-based digital media was included in the category of "feasible" to be used as an instructional learning media. The seventh study conducted shows that e-books assisted by flipbooks provide opportunities for the college student to participate actively and help build their knowledge during the pandemic to achieve an increase in college student analytical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing data on environmental change, its causes, and impacts on life, and CC 4.11 Formulating ideas for solving problems of environmental changes that occur in the surrounding environment so that the components in the learning aspects meet standardization. This can cause the developed Flipbook to play an optimal role in presenting learning material that accommodates understanding of students' concepts, skills, and attitudes (Perdana et al, 2021). Based on Table 5, the average percentage of language feasibility obtained is 92% and is categorized as very valid.…”
Section: Theoretical Feasibilitymentioning
confidence: 99%